2018
DOI: 10.1016/j.celrep.2018.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Activation of EphB2 Forward Signaling Enhances Memory Consolidation

Abstract: EphB2 is involved in enhancing synaptic transmission and gene expression. To explore the roles of EphB2 in memory formation and enhancement, we used a photoactivatable EphB2 (optoEphB2) to activate EphB2 forward signaling in pyramidal neurons in lateral amygdala (LA). Photoactivation of optoEphB2 during fear conditioning, but not minutes afterward, enhanced long-term, but not short-term, auditory fear conditioning. Photoactivation of optoEphB2 during fear conditioning led to activation of the cAMP/Ca responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
(58 reference statements)
3
19
0
Order By: Relevance
“…We demonstrated that EphB2 played an important role in SI-induced memory forgetting, which strengthens the evidence that EphB2 is involved in enhancing synaptic transmission, and the gene expression is believed to underlie memory formation 39,41,54,55 . EphB2 interacts with NMDA receptors and regulates excitatory synapse formation.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We demonstrated that EphB2 played an important role in SI-induced memory forgetting, which strengthens the evidence that EphB2 is involved in enhancing synaptic transmission, and the gene expression is believed to underlie memory formation 39,41,54,55 . EphB2 interacts with NMDA receptors and regulates excitatory synapse formation.…”
Section: Discussionsupporting
confidence: 83%
“…Together with the accumulating evidences, EphB2 mediates the excitatory synaptogenesis during development and coordinates synaptic plasticity by controlling the localization and function of glutamate receptors 27,59 . Previous studies also show that EphB2 signal is related to anxiety disorders 62 , autism 63,64 , and cognitive dysfunction 41,65 . Our study expands the understanding of the (see figure on previous page) Fig.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Indeed, EphB2 loss was shown to attenuate LTP (Grunwald et al, 2001;Henderson et al, 2001) and to impair LTD (Grunwald et al, 2001). While the loss of EphB2 function impairs long-term memory formation, photo-activation of EphB2 using optogenetics during fear conditioning learning enhances long-term memory (Alapin et al, 2018). However, our previous study showed no effects of astrocytic ephrin-B1 deletion on LTP induction and consolidation in the adult hippocampus of naïve WT and KO mice (Koeppen et al, 2018).…”
Section: Discussionmentioning
confidence: 91%
“…In a separate cohort of mice, after bilateral stereotactic injection of AAV constructs at both regions, guide steel cannulas (23gauge) were inserted 1 mm above the aIC, to allow local delivery of CNO upon recovery. Cannula placement was secured using dental cement as previously described (Alapin et al, 2018). After viral delivery and appropriate cleaning and suturing (Vetbond) of the exposed skull, animals were administered an additional intraperitoneal dose of 0.5 mg/kg Norocarp, as well as 0.5 mg/kg Baytril (enrofloxacin).…”
Section: Surgery and Viral Injectionmentioning
confidence: 99%